ϴзбекстанның тунғыш профессоры - Сейтмуратов, Қ (FAN va JAMIYAT, 2023)
The article deals with the issues of Jadid and educational activities and pedagogical thoughts of the prom- inent Uzbek teacher and poet Abdirauf Fitrat.